(untitled) (Research, Society and Development, 2021)
The russian Alexander Romanovich Luria, commonly credited as the father of modern neuropsychology, was responsible for the greater understanding of human psychic and behavioral processes. Through studies on brain injuries, Luria tried to generate an integrative and logical theory for brain functions, in other words, to develop further technical studies on mental functions. To this end, he divides the general brain activities into three units, the first having the function of maintaining surveillance, the second being responsible for obtaining, processing, integrating and storing the information provided by the environment, and the third unit is responsible to plan, execute and direct the pattern of human behavior. Thus, the aim of this study is to review the frontal lobe (FL) neuropsychology and to associate it with the third functional unit of Luria. The references of the book "The Working Brain" were used. In the end, it was possible to conclude from Luria’s conceptions that the third functional unit is responsible for the stimuli synthesis, preparation for action, program constructions, verification of the activity’s ways, generation of activation process linked to the most complex conscious actions and a speech collaboration.